Features of hedging strategies performed by the Federal Reserve Chair in press conferences - Deng, Zhujun; Mohamad Ali, Afida; Mohd Zin, Zaid (Academy Publication, 2024)
This study examined the pragmatic functions of hedging strategies used by the Federal Reserve System (Fed) Chair during press conferences. The Fed’s significant influence on U.S. monetary policy and global financial markets makes its communication methods crucial yet linguistically underexplored. This study employed a mixed-methods approach to examine the frequency and types of hedges, their situational usage, and pragmatic functions. The findings revealed a notable use of approximators and shields to adapt to the complexities of financial communication, with adaptors and plausibility shields being the most common. The Fed Chair employed hedging strategies to address sensitive economic issues, uncertain policies, and matters affecting financial markets and public perception. These hedging strategies were used to mitigate potential criticism, enhance flexibility, soften the tone, maintain credibility, ensure effective information delivery, and improve politeness. The study contributed to the understanding of linguistic hedging strategies in financial communication and underscored the strategic use of language in economic policy-making and financial stability.